Transforming Nursing, Midwifery and Health Professions' (NMaHP) roles : pushing the boundaries to meet health and social care needs in Scotland.: pushing the boundaries to meet health and social care needs in Scotland. Developing the general practice nursing role in integrated community nursing teams. Paper 06, (2018) - Unknown
No abstract available